2002
DOI: 10.1007/s00213-001-0990-1
|View full text |Cite
|
Sign up to set email alerts
|

Distal and proximal pre-exposure to ethanol in the place conditioning task: tolerance to aversive effect, sensitization to activating effect, but no change in rewarding effect

Abstract: These studies suggest that both forms of pre-exposure reduced ethanol's aversive effect, but had no impact on ethanol's rewarding effect. In general, the detrimental effects of pre-exposure on CPA are explained best in terms of a reduction in ethanol's efficacy as an aversive unconditioned stimulus (i.e. tolerance), although explanations based on other types of associative interference are also possible. The failure to affect CPP with pre-exposure treatments that reduced or eliminated CPA suggests that these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 53 publications
(100 reference statements)
6
64
1
4
Order By: Relevance
“…The results of Experiment 1 showing different patterns of neural activation for Before-S and After-S mice are consistent with the hypothesis that ethanol-induced CPP and CPA are mediated by different underlying processes (Cunningham et al, 2002). In general, the FOS profiles for these two groups differ in that Before-S mice had more activation in the BST and DMH compared to After-S mice (as well as both control groups), and FOS differences in the VTAant approached significance at p < .06.…”
Section: Comparison Of Before and After Groupssupporting
confidence: 85%
See 1 more Smart Citation
“…The results of Experiment 1 showing different patterns of neural activation for Before-S and After-S mice are consistent with the hypothesis that ethanol-induced CPP and CPA are mediated by different underlying processes (Cunningham et al, 2002). In general, the FOS profiles for these two groups differ in that Before-S mice had more activation in the BST and DMH compared to After-S mice (as well as both control groups), and FOS differences in the VTAant approached significance at p < .06.…”
Section: Comparison Of Before and After Groupssupporting
confidence: 85%
“…More specifically, pre-CS ethanol produces CPP whereas post-CS ethanol produces conditioned place aversion (CPA) (Cunningham and Henderson, 2000;Cunningham et al, 1997). Because these motivationally opposite behaviors are thought to be independently mediated (Cunningham et al, 2002), Before-S group mice were expected to have different patterns of FOS activation than After-S group mice, and both paired groups were expected to differ from unpaired-drug (Delay-S group) and drug-naive (Naïve-S group) control mice. On the final day, all mice were first tested for conditioned changes in activity after exposure to the CS+ and saline.…”
Section: Introductionmentioning
confidence: 99%
“…Experiment 1 suggested that this interference effect was unique to the 5-min pre-exposure interval since pre-exposure at 15 min did not interfere with place preference when compared to a group that was matched for overall ethanol exposure, but received the extra ethanol injection 60 min after each trial. Although the place preference observed after pretreatment with ethanol 30 min before the trial was statistically marginal, the general conclusion of no interference at pretreatment intervals longer than 5 min is certainly consistent with the previous report of no interference with ethanol pretreatment at 65 min (Cunningham et al, 2002). The finding that pre-exposure to a saline injection 5 min before each CS+ trial had no effect on place preference (Experiment 2) argues against an interpretation of the interference effect that simply appeals to stress induced by handling and injection.…”
Section: Discussionsupporting
confidence: 90%
“…However, same drug pre-exposure had absolutely no effect on acquisition of conditioned place preference produced by pre-CS injection of the same ethanol US (Cunningham et al, 2002). In both studies, the pretreatment injection occurred 65 min before the conditioning trial injection.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation